Evaluation of the range of conformity of the performance of the administrations of the Palestinian universities in the Gaza Strip with the principles of governance and some criteria of excellence - a field study - Nassar, Anwar Shehadeh (Arab Journal for Sciences and Research Publishing, 2017)
The study aimed to assess the performance of the Palestinian universities administrations in the Gaza Strip match with the principles of corporate governance and some standards of excellence from the viewpoint of the faculty members, the study used a descriptive and analytical approach, were applied a questionnaire consisting of (31) items on a sample consisting of the number of study (292) faculty member teaching, selected a stratified random manner relative of universities (Al-Azhar , Islamic, and maximum), and increased by 30.2%, in the second semester 2015/2016 m. The results revealed that the study sample approval on the reality of Excellence Palestinian universities education management in the light of the application of the principles of corporate governance at universities in Gaza as a whole amounted to (3.73), as a percentage of (74.72%) significantly, came the scope of participation the first prize with a mean (4.27), and the proportion of a percentage of (85.4%) very much, and in the second area of transparency was an arithmetic mean was (3.92), and the percentage of (78.4%) significantly, and in third place the field of effectiveness and efficiency came an arithmetic mean was (3.76), and the percentage of (75.2%) significantly, and in the fourth field Rashadh The decision-making with a mean was (3.41), and the percentage of (68.2%) significantly, and in last place the field of competitiveness came with a mean was (3.32), as a percentage of (66.4 %) moderately. The findings revealed that there were no statistically significant differences in the study sample estimates of the degree of evaluating the performance of the Palestinian universities administrations in the Gaza Strip match with the principles of corporate governance and some standards of excellence from the viewpoint of faculty members attributed to the sex variable and variable universities differences, while found statistically significant differences in the sample members study estimates due to the variable years of experience for the benefit of years of experience of 11 years and above. The study made a number of recommendations.
Keywords: Palestinian University Administrations; Principles of Governance; Standards of Excellence; Palestinian Universities